Strategi Meningkatkan Produktivitas Karyawan UMKM: Studi pada Usaha Pentol Goreng Izza - Aril Ali Akbar; Afiq Faqih Widad (Jurnal Pelita Nusantara, 2026)
This study aims to analyze employee productivity conditions and formulate strategies to improve productivity at Pentol Goreng Izza business. Employee productivity is an important factor in supporting operational efficiency, product quality, and business sustainability. This study employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation involving the business owner and employees. The findings indicate that employee productivity has not been optimal due to limited work skills, low utilization of production technology, ineffective incentive systems, and inefficient time management. Strategies that can be implemented to improve productivity include skills training, the use of technology appropriate to business needs, performance-based incentives, a more structured work system, and the application of honesty, responsibility, fairness, and cooperation values in the workplace. The implementation of these strategies is expected to increase employee productivity so that the business can grow efficiently, competitively, and sustainably.